Sex differences in presentation of pheochromocytoma and paraganglioma - Ali, Nora Azin; Calissendorff, Jan; Falhammar, Henrik (Frontiers in Endocrinology, 2025)
PurposeThe aim of the study was to investigate sex differences in presentation of pheochromocytomas and paragangliomas (PPGLs).MethodsThis is a retrospective cohort study including 183 patients with confirmed PPGL (females n=100, pheochromocytoma n=156) between year 2005 and 2023, attending Department of Endocrinology, Karolinska University Hospital, Stockholm. The collected data included the mode of presentation, symptoms, biochemical, genetic and histopathological test results.ResultsThe mean age at surgery/diagnosis was 54.9 ± 17.0 years. Sweating was more common in females compared to males (44% vs 23%, p=0.003), and also takotsubo syndrome (10% vs 0% p=0.002). Males, on the other hand, were more likely to experience pallor (16% vs 4%, p=0.009), and were more often diagnosed due to investigations of a suspected PPGL (31% vs 18%, p=0.039) although no difference was found in the classic triad (sweating, palpitations and headache). Left-sided pheochromocytoma was more common among males than females (48% vs 29%, p=0.009). No differences between sexes were found in biochemical, genetical or histopathological results, or presence of metastasis at diagnosis.ConclusionsThe reported symptoms by patients with PPGL were generally similar between the sexes, except for pallor and sweating. Takotsubo syndrome was more common among females. More males with PPGL were found based on suspicion than females. Further research into sex differences in various aspects of PPGL should be pursued.